Acute Increases in Serum Creatinine After Starting Angiotensin-Converting Enzyme Inhibitor-Based Therapy and Effects of its Continuation on Major Clinical Outcomes in Type 2 Diabetes Mellitus: The ADVANCE Trial. Issue 1 (January 2019) - Ohkuma, Toshiaki; Jun, Min; Rodgers, Anthony; Cooper, Mark E.; Glasziou, Paul; Hamet, Pavel; Harrap, Stephen; Mancia, Giuseppe; Marre, Michel; Neal, Bruce; Perkovic, Vlado; Poulter, Neil; et al.
Abstract : Discontinuation of angiotensin-converting enzyme (ACE) inhibitor is recommended if patients experience ≥30% acute increase in serum creatinine after starting this therapy. However, the long-term effects of its continuation or discontinuation on major clinical outcomes after increases in serum creatinine are unclear. In the ADVANCE trial (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation), 11 140 diabetes mellitus patients were randomly assigned to perindopril-indapamide or placebo after a 6-week active run-in period. The current study included 11 066 participants with 2 serum creatinine measurements recorded before and during the active run-in period (3 weeks apart). Acute increase in creatinine was determined using these 2 measurements and classified into 4 groups: increases in serum creatinine of <10%, 10% to 19%, 20% to 29%, and ≥30%. The primary study outcome was the composite of major macrovascular events, new or worsening nephropathy, and all-cause mortality. An acute increase in serum creatinine was associated with an elevated risk of the primary outcome ( P for trend <0.001). The hazard ratios were 1.11 (95% CI, 0.97–1.28) for those with an increase of 10% to 19%, 1.34 (1.07–1.66) for 20% to 29%, and 1.44 (1.15–1.81) for ≥30%, compared with <10%. However, there was no evidence of heterogeneity in the benefit of randomized treatment effects on the outcome across subgroups defined by acute serum creatinine increase ( P for heterogeneity=0.94). Acute increases in serum creatinine after starting perindopril-indapamide were associated with greater risks of subsequent major clinical outcomes. However, the continuation of angiotensin-converting enzyme inhibitor-based therapy reduced the long-term risk of major clinical outcomes, irrespective of acute increase in creatinine. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00145925. Abstract : Supplemental Digital Content is available in the text.